Prevalence, Viewpoints, and Encounters with Cyberterrorism among College Students - Al-Badayneh, Diab M. (Journal of Ecohumanism, 2024)
This research aims to describe prevalence, perspective on cyberextremism and encounters of cyberextremism among college students. A sample of 1000 Tafila Technical University (TTU) students ) representing 12 Jordanian governates, found that 45.4% were males and 54.6% were females from 12 Jordanian governorates. Science colleges and arts and social colleges split the sample almost equally (49.6% vs. 50.4%), respectively. All students are using the internet, and most of them use it intensively (73%), compared to regular use (27%). The study found that less than half of the sample described online extremism as hate speech, violence, cyberbullying, sexual pornography, indirect hate speech, assaults, and post-support extremism. Students perceived several procedures to encounter cyberextremism, including closing websites, fines, criminalizing content, holding websites responsible for compensation, establishing a minimum age for viewing extremist content, removing hardening material, and compensation. Males had a higher mean of cyberextremism than females. ANOVA analysis showed significant differences between external attribution and cyberextremism, internal attributions, and no significant differences between males and females.